2020
DOI: 10.3847/1538-4357/ab76c4
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of PSR J1640+2224: A Neutron Star Born Massive?

Abstract: PSR J1640+2224 is a binary millisecond pulsar (BMSP) with a white dwarf (WD) companion. Recent observations indicate that the WD is very likely to be a ∼ 0.7 M ⊙ CO WD. Thus the BMSP should have evolved from an intermediatemass X-ray binary (IMXB). However, previous investigations on IMXB evolution predict that the orbital periods of the resultant BMSPs are generally < 40 days, in contrast with the 175 day orbital period of PSR J1640+2224. In this paper, we explore the influence of the mass of the neutron star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…However, it should be noted that the value from NG12.5 is better than 1σ consistent with the extrapolated value from NG11, whereas the value from the wideband analysis is ∼ 2σ consistent with the extrapolated value from NG9. Fonseca et al (2016) followed up on NG9 and suspected that J1640+2224 is a massive neutron star (see also Deng et al 2020); the improvements on the mass measurements will be presented elsewhere.…”
Section: J1640+2224mentioning
confidence: 99%
“…However, it should be noted that the value from NG12.5 is better than 1σ consistent with the extrapolated value from NG11, whereas the value from the wideband analysis is ∼ 2σ consistent with the extrapolated value from NG9. Fonseca et al (2016) followed up on NG9 and suspected that J1640+2224 is a massive neutron star (see also Deng et al 2020); the improvements on the mass measurements will be presented elsewhere.…”
Section: J1640+2224mentioning
confidence: 99%
“…Dong et al (2014)) found that both “outliers” of BH XRBs and bright AGNs follow a steeper fundamental plane of black hole activity. Coriat et al (2011) argued that the two fundamental planes are regulated by radiatively inefficient (e.g., ADAF) and radiatively efficient accretion processes (e.g., SSD + corona), respectively, if we assume the jet launching and radio radiation behave identically (see also, Deng et al 2020; Gao et al 2011a; Fu et al 2020; Li et al 2016; Zhu et al 2016; Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments will provide an emerging understanding of nuclear matter EOS and the transition to deconfined quark matter. Hopefully, the high density behavior of the NS EOS can be determined soon, shedding light on many unsolved problems in nuclear physics and high-energy astrophysics [e.g., 310,311,312,313,314,315].…”
Section: Summary and Perspectivesmentioning
confidence: 99%